Behaviour of vertically loaded steel beams under a travelling fire. (October 2022) - Shakil, Saani; Lu, Wei; Puttonen, Jari
Abstract: As the structural response to a time and space dependent non-uniform temperature field is challenging to manage by code-based design, the behaviour of steel beams exposed to a travelling fire was simulated numerically in this paper. The finite element (FE) models for both thermal and mechanical analyses were validated by two benchmark tests and used to study the effect of uniform and non-uniform thermal exposures and different steel grades on the response of steel beams. The developed five-stage mechanism well characterized the response of the beams exposed to the travelling fire. For the beam in the elastic range, the heating-cooling cycles of gas temperatures induced cyclic axial forces, but the cyclic nature of structural responses was cushioned by material plasticity. For the beams stressed into the plastic range, the repetitions of cycles in axial response created residual deformations that induced catenary action in the beams at lower temperatures. The local heating of the critical sections made the beams more prone to a runaway failure than the uniform heating of the whole beam. Compared to the mild steel beams, the axial force response of the HSS beams showed higher axial compression forces and fluctuated more. The critical temperatures based on the deformation or strength criterion were consistent for the beams with the load ratio of 0.3. However, for designing the beam with the load ratio of 0.5, critical temperature of 350 °C or the strength criteria based on the proportional limit are recommended as the catenary action was activated at low temperatures. These recommendations can be used as a guide for practical design.